DETERMINAN EFEKTIVITAS AUDITOR INTERNAL PEMERINTAH DAERAH KABUPATEN SE-JAWA TENGAH - Muhammad Akram Naufal; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
The  aim  of  this  study  was  to  obtain  empirical  evidence  about  the  influence  of  Professional Expertise, Work Quality Auditor, Auditor Independence Organization, Ascension Career Auditor, and Top Management Support of the effectiveness of internal auditors. It also obtain empirical evidence of how much influence the professional ability, Work Quality Auditor, Auditor Independence Organization, career and promotion, as well as the support of the top management of the Effectiveness of Internal Auditors simultaneously. This study uses the inspectorate auditor regencies in Central Java with samples taken sebanayak 33 respondents. The data obtained were then  analyzed  using  descriptive  statistical  analysis  of  technical,  test  data  quality,  classic assumption test, and multiple linear analysis.